An Analysis of Camera Translator Application’s Results in Perspective of Nababan’s Theory - Rizki Adha; Muhammad Dalimunthe; Sholihatul Hamidah Daulay (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the quality of the Camera Translator application based on the perspective of Nababan’s theory. The reason for conducting this research is because of the importance of understanding the quality of the camera translator application which is increasingly used in everyday life and education, especially to overcome limited foreign language skills. The method used in this research is descriptive qualitative. The research instruments used include the Camera translator application and translation quality assessments based on Nababan theory indicators, namely accuracy, readability, and acceptability. The data source in this research is written text, a part of a short story entitled “April in Moscow” translated using a camera translator application. The research data is in the form of text translation results from English to Indonesian taken by taking pictures of the text to be translated. The research results show that camera translator applications have varying accuracy, readability, and acceptability levels. From data sources totaling 63 sentences from part of the short story